Developing and validating a digital literacy assessment: bridging the digital divide among adolescents in Sabah, Malaysia - Shakira Arbine; Mohamad Shukri Abdul Hamid (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigates the computer literacy of adolescents in Tawau, Sabah, challenging the notion that all "Digital Natives" are inherently proficient in technology. Despite growing up in a digital era, many youths in Tawau demonstrate limited skills in essential software like Microsoft Office, highlighting a significant digital divide. The study began by identifying key themes from existing instruments, leading to the development of a tailored assessment tool for Tawau, Sabah. This tool underwent rigorous validation through Rasch analysis, confirming its effectiveness in measuring various dimensions of computer literacy, including basic skills and Microsoft Office proficiency. The findings provided insights into the instrument’s performance and scoring, refining its items and confirming reliability and validity. Ultimately, the index quantifies computer literacy by aggregating scores across categories, offering a reliable measure of adolescents' digital competencies in Tawau. This research contributes to a broader understanding of the digital divide and informs strategies to improve computer literacy in similar contexts. The study’s implications underscore the importance of policy adjustments to bridge the digital gap, especially in underserved regions like Tawau.